Collaborative innovation networks: harnessing external expertise for growth in developing Bancassurance channel - Iqbal, Muhammad Nawaz; Jan, Muhammad Tahir (IGI Global Scientific Publishing, 2025)
This chapter reveals that in the current environment for financial services which is dynamic and competitive; that open innovation is the compelling strategies for growth in the Bancassurance sector. This chapter is devoted to the modern vision of CINs in the context of Bancassurance and focuses on the involvement of outside knowledge from various sources, including fintech start- ups, academic institutions, as well as research centers that might be involved in the design of the Bancassurance business model. Through using CINs, existing concepts, new idea, advanced technology and skill can be introduced into the banks and insurance companies to enhance the speed of creating new innovative products as customer’s need arise. This chapter focuses on different issues connected with the usage of intellectual property management, and cooperation between organizations and external technologies. Some possible criteria for practical implementation of the strategy are considered based on the analysis of the most significant factors influencing Bancassurance development.